EFEKTIVITAS PENCEGAHAN BADAN NARKOTIKA NASIONAL PROVINSI JAWA TENGAH DALAM PENANGANAN PERMASALAHAN NARKOBA DI WILAYAH JAWA TENGAH - M. Tha’at Amrullah; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
he drug problem in Central Java is handled by the Central Java Provincial National Narcotics Agency (BNNP) through the Community Prevention and Empowerment Sector (P2M) with various preventive measures, such as: dissemination of information, advocacy, socializing drugs, empowering community participation (PSM) and empowering alternatives. (PA), as well as other supporting activities. The research method used by the author in this study is a qualitative method, which includes several aspects, namely: goal achievement, integration, and adaptation. The informants chosen by the authors in this study are : the Head of the Community Prevention and Empowerment Division, the Head of the Prevention Section, and the Head of the Community Empowerment Section. The results showed that the Effectiveness of the Prevention and Community Empowerment Sector was quite effective, although not optimal. The effectiveness of P2M can be seen from the aspects of effectiveness, namely: goal achievement, integration, and adaptation. Some of the obstacles faced are: P2M field human resources which are still lacking and limited to cover the entire area of Central Java which is so wide, the lack of a prevention fleet in the form of urine test trucks and drug prevention cars, and the annual budget that is obtained is insufficient to carry out a work design existing, causing the prevention and community empowerment process to not run optimally. It is recommended that the Community Prevention and Empowerment Sector be more innovative and active by conducting socialization through other media, such as: magazines, radio, regional television, or websites belonging to provincial offices, seeking and collaborating with relevant stakeholders as an effort to suppress the existing budget, and evaluate the results of the performance taken so that the steps in the Prevention and Community Empowerment Sector in the future can be better and optimal. Keywords: Effectiveness,